Analysis of students discipline on the learning process at elementary school - Angita, Roza; Witanto, Yuli (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The problem of student discipline is an important thing that must be considered. It is known that in the learning process there are various discipline problems committed by students such as skipping school, arriving late, disobeying school rules and regulations, not doing the assigned tasks, not focusing on learning, etc. often occur. If these various problems are left unchecked, they will interfere with the student learning process and have an impact on their learning achievement. This study aims to determine the problems of student discipline in grade V of SD Negeri 2 Ngampel during the learning process and its impact on learning achievement, as well as the efforts given by teachers in instilling the value of discipline towards students. This research was aimed at teachers and grade V students at SD Negeri 2 Ngampel. This research uses a qualitative approach with data collection techniques obtained from interviews, observations, questionnaires and documentation. Based on the results of the analysis, it can be concluded that the discipline of grade V students at SD Negeri 2 Ngampel during learning is quite good. However, it needs to be improved again when viewed from several existing discipline problems. A teacher plays an important role in striving to instill the value of discipline to students so that the learning process can run effectively